Optimizing Social Emotional Learning (SEL) in Elementary School Learning to Strengthen Students' Character and Psychological Well-Being - Esmi Tsalsa Sofiawati; Ardi Cahyadireja; Asep Aonudin; Navira Nailal Ula (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
21st-century learning demands strengthening the character and psychological well-being of students from elementary school. Social Emotional Learning (SEL) is seen as a strategic approach relevant to the Pancasila Student Profile while addressing students' social-emotional challenges in the digital era. This study aims to measure the influence of SEL on students' character and psychological well-being, describe its implementation practices in schools, and formulate effective optimization strategies. The study used mixed methods with a sequential explanatory design. Quantitative data were obtained through questionnaires from 180 students, analyzed statistically, and then strengthened by interviews, observations, and document studies. The results of the quantitative analysis showed an average score of student character M=3.27 (SD=0.33), psychological well-being M=3.15 (SD=0.35), and SEL M=3.20 (SD=0.40) on a scale of 1–4, all in the high category. Qualitative data confirmed that SEL practices are beginning to appear in learning despite still being hampered by teacher understanding and school support. These findings can be applied by teachers to integrate SEL into daily learning, enrich the theory on the relationship between SEL and character and psychological well-being in the elementary school context, and open up opportunities for further research related to long-term SEL implementation and evaluation strategies.